Racial disparities in mortgage lending: New evidence based on processing time - Bin Wei; Feng Zhao (Federal Reserve Bank of Atlanta, 2022)
This paper examines racial disparities in mortgage processing time prior to the global financial crisis. We find that Black borrowers are underrepresented and experience a longer processing time than White borrowers among the mortgages securitized by government-sponsored enterprises. At the same time, Black borrowers are overrepresented and face a similar processing time among privately securitized mortgages. Additionally, Black borrowers are strongly associated with the faster segments of mortgage markets, faster lenders within each segment, and the types of loan products that are processed faster, all of which subsequently experienced higher defaults.
Keywords: G01; G21; G23; R30; 330; processing time; lending standards; racial disparities; mortgage loans; Hypothek; Ethnische Diskriminierung; Schwarze Menschen; USA